Una aproximación a la historia medieval en Galicia entre los años 2007 y 2017 - Álvarez García, Carmen (Historiografías, 2020)
This article attempts to identify the lines of research of the works produced in Galicia (Spain) between 2007 and 2017. We shall examine articles and books written by Galician medievalists and classify them within the so called Galician historiographic field. The different trends both the emergent, minority and consolidated ones have also been included. As we explain there, this production takes part of the evolution of the Spanish and European historiography in that period. Keywords Galician historiography, medieval history, political history, social organization of the territory.